Product Inhibition and pH Affect Stoichiometry and Kinetics of Chain Elongating Microbial Communities in Sequencing Batch Bioreactors - Allaart, Maximilienne Toetie; Stouten, Gerben Roelandt; Sousa, Diana Z.; Kleerebezem, Robbert (Frontiers in Bioengineering and Biotechnology, 2021)
Anaerobic microbial communities can produce carboxylic acids of medium chain length (e.g. caproate, caprylate) by elongating short chain fatty acids through reversed β-oxidation. Ethanol is a common electron donor for this process. The influence of environmental conditions on the stoichiometry and kinetics of ethanol-based chain elongation remains elusive. Here, a sequencing batch bioreactor setup with high-resolution off-gas measurements was used to identify the physiological characteristics of chain elongating microbial communities enriched on acetate and ethanol at pH 7.0±0.2 and 5.5±0.2. Operation at both pH-values led to the development of communities that were highly enriched (>50%, based on 16S rRNA gene amplicon sequencing) in Clostridium kluyveri related species. At both pH-values, stably performing cultures were characterized by incomplete substrate conversion and decreasing biomass-specific hydrogen production rates during an operational cycle. The process stoichiometries obtained at both pH-values were different: at pH 7.0, 71±6% of the consumed electrons were converted to caproate, compared to only 30±5% at pH 5.5. Operating at pH 5.5 led to a decrease in the biomass yield, but a significant increase in the biomass-specific substrate uptake rate, suggesting that the organisms employ catabolic overcapacity to deal with energy losses associated to product inhibition. These results highlight that chain elongating conversions rely on a delicate balance between substrate uptake- and product inhibition kinetics.